An intersection theorem in L-convex spaces with applications - Lu, Haishu; Tang, Deshan (Journal of mathematical analysis and applications, 2005)
A new intersection theorem is obtained in L-convex spaces without linear structure. As its applications, a fixed point theorem, a maximal element theorem, a coincidence theorem, some new minimax inequalities and a saddle point theorem are given in L-convex spaces. Our results generalize many known theorems in the literature.